Instructional Psychology: Past, Present, and Future - GLASER, R. (Pedagogische Studiën, 1981)
The history of instructional psychology is traced through Thorndike, Dewey, Skinner, and recent developments. At the present time, instructional psychology, with the methods and concepts of cognitive psychology, is focusing on the acquisition of competence.Researchers are examining cognitive processes required in advanced levels ofreading and text comprehension; the computation and advancedproblemsolvingskills needed in mathematics; the skills of learningassessed by aptitude tests; and the effects of the interaction between initial ability and classroom processes onschool achievement. The emerging field of instructional psychology can be describedin terms offour majorcomponents: the initial state of the learner, the nattereof the competence to be attained, the transition processes between these two stages, and ways ofassessing andmonitoring performance changes in the acquisition ofcompetence. Principles that should guide the futuredevelopment ofa psychology of Instruction are discussed.